Strategi Guru Mengefektifkan Kegiatan Pembelajaran Sosiologi pada Penerapan Kurikulum Merdeka di Sekolah Menengah Atas Negeri 2 Pandeglang - Puja Damar Wulan; Wahid Abdul Kudus; Dema Tesniyadi (Universitas Lambung Mangkurat, 2024)
Abstrak The implementation of differentiated learning in sociology learning in the implementation of an independent curriculum at SMA Negeri 2 Pandeglang found several problems. Among them: students feel bored; lack of cooperation between students in each group; only a few students are active; and lack of interactive. The research aims to get an overview of the teacher’s strategy to streamline sociology learning activities in the implementation of the independent curriculum at SMA Negeri 2 Pandeglang. The research used a qualitative method with a descriptive approach. Data collection techniques were carried out through observation, interviews and documentation. The research was conducted at SMA Negeri 2 Pandeglang, Pandeglang Regency. Data analysis techniques used data reduction, data presentation and conclusion drawing or verification. The results showed that the teacher's strategy to streamline sociology learning activities in implementation the independent curriculum at SMA Negeri 2 Pandeglang was through differentiated learning. Differentiated learning is inseparable from several stages: the learning planning stage includes the implementation of diagnostic assessments, preparation of teaching modules, preparation of learning media and preparation of teaching materials. The learning implementation stage includes opening activities, core activities and closing activities. Various ways: appreciation and apperception, ice breaking, personal approach, varied learning methods and the use of mapping class techniques. Supporting factors: students motivation to learn, supportive learning media and teacher enthusiasm. Inhibiting factors: limited time, not all students actively participate and differences in students' abilitiy to understand learning.